Alpha spectroscopy and X-ray induced photocurrent studies of a SC CVD diamond detector fabricated with PLD contacts. (November 2019) - Abdel-Rahman, Mohamed A.E.; Lohstroh, Annika; Bryant, Peter
Abstract: Using amorphous Carbon blended with Nickel (C/Ni) as electrodes for a polycrystalline diamond radiation detector (PC-C/Ni) was demonstrated previously as a novel technique to produce near-tissue equivalent X-ray dosimeters. In this project, we introduce the first characterisation of a (Chemical Vapour Deposited) single crystal diamond sandwich detector (with thickness of 0.4 mm) fabricated with this technique, labelled SC-C/Ni. To examine the performance of pulsed laser deposition (PLD) C/Ni as an electrode, alpha spectroscopy measurements and X-ray induced photocurrent measurements were studied as a function of the applied bias at room temperature and compared with those of the aforementioned PC-C/Ni. The alpha particle spectroscopy measurement data allows us to differentiate between electron and hole contributions to the charge transport signal, whilst the X-ray data was investigated in terms of dose rate-linearity, sensitivity, signal to noise ratio (SNR) and photoconductive gain. In the case of electron sensitive alpha induced signals, a Charge Collection Efficiency (CCE) higher than 90% has been observed at a bias of −40 V and 100% CCE at −300 V, with energy resolution of ∼3% for 5.48 MeV alpha particles. The sample showed very poor spectroscopy performance for hole sensitive signals up to 200 V. The X-ray induced photocurrents show a high SNR of ∼7.3 × 10 3, an approximately linear relationship between the photocurrent versus dose rate and a sensitivity of 4.87 μC/Gy.mm 3 . The photoconductive gain of SC-C/Ni is calculated to be ∼20, this gain calculation might be explained by trapping effects as investigated in the alpha spectroscopy measurements. Highlights: Single crystal diamond detector with novel pulsed laser deposited low Z electrodes. sAlpha spectroscopy and X-ray photocurrent characterisation of the novel device. Asymmetric charge transport properties with superior electron transport. X-ray induced photocurrents show a Signal to noise ratio of 7 × 10 3 and sensitivity of 4.87 μC.Gy mm -3 . Photoconductive gain is approx. 20, possibly caused by trapping effects.